IMPROVING STUDENTS’ CAREER MATURITY THROUGH VIDEO-BASED CAREER INFORMATION SERVICES AT SMP NEGERI 1 BATANG KUIS - Mustia, Ardilla Indah; Darwin, Muhammad Riza (Jurnal Kopendik, 2026)
This study aimed to improve the career maturity of Grade IX students at SMP Negeri 1 Batang Kuis through the implementation of video-based career information services. The study employed Classroom Action Research based on the Kemmis and McTaggart model, which was carried out in the pre-cycle, Cycle I, and Cycle II stages. The participants were 32 students. Data were collected through a career maturity questionnaire, observation sheets, and documentation, and were analyzed using descriptive comparative techniques. The results showed that the students’ mean career maturity score increased from 58.6 in the pre-cycle to 69.4 in Cycle I and 79.4 in Cycle II. The dominant category also shifted from moderate to high. The percentage of students in the high category increased from 13% in the pre-cycle to 22% in Cycle I and 59% in Cycle II, while the low category decreased from 31% to 13% and 3%, respectively. Observation results also indicated improvement in students’ focus on the material, participation in asking or answering questions, and seriousness in completing tasks, increasing from 2.3, 2.0, and 2.2 in the pre-cycle to 3.6, 3.4, and 3.7 in Cycle II. These findings indicate that video-based career information services are effective in improving students’ career maturity.